Maternal high-fat diet sex-specifically alters placental morphology and transcriptome in rats: Assessment by next-generation sequencing. (March 2019) - Lin, Yu-Ju; Huang, Li-Tung; Tsai, Ching-Chou; Sheen, Jiunn-Ming; Tiao, Mao-Meng; Yu, Hong-Ren; Lin, I-Chun; Tain, You-Lin
Abstract: Introduction: Maternal nutrition is an extremely important health issue. We evaluated the impact of maternal high fat diet (HFD) on pregnancy outcomes, elucidated how the rat placenta and fetus respond to diet manipulation based on fetal sex, and identified candidate genes and pathways. Methods: Rats were fed a normal or HFD diet for 10 weeks before conception and during gestation. The placenta was collected on gestational day 21 and sexed. Placental histology was analyzed and placental candidate genes and pathways were identified using whole-genome RNA next-generation sequencing. Results: Pup weights in both sexes from HFD dams were reduced. The weight of the placenta from the HFD group was also decreased in both sexes, but changes in placental layer distributions were only significant for female fetuses. Maternal HFD altered the placental transcriptome in a sex-specific manner. Activation of the placental renin-angiotensin system (RAS) by maternal HFD was associated with fetal growth restriction in both fetal sexes. Conclusions: The placenta reacts to maternal HFD by altering the placental layer distribution and gene expression in a sex-specific manner. The male placenta in late gestation is thought to exhibit greater plasticity relative to the female placenta; however, fetuses of both sexes exhibited similar growth restriction. Our data reveal an association between the placental RAS and HFD-induced fetal growth restriction. Highlights: Pup weights in both sexes from HFD dams exhibit similar growth restriction pattern. HFD altered the placental histology and transcriptome in a sex-specific manner. Activation of placental RAS by maternal HFD was associated with fetal growth restriction.